Reactions of iron- and zinc-fuelled pyrotechnic systems - Tribelhorn, Michael John (Rhodes University, Faculty of Science, Department of Chemistry, 1995)
A major industrial use of pyrotechnic compositions is as delay fuses in electric detonators. Suitable delay times may be achieved through (i) choice of chemical components (ii) adjustment of composition of the system chosen and, finally, (iii) adjustment of the length of fuse used. This study forms part of a survey of binary fuel/oxidant combinations in an attempt to provide some fundamental information on the first step above: (i) choice of chemical components. The complete survey has included studies of a single fuel in combination with one of a variety of oxidants, and studies of the oxidation of one of several different fuels separately by barium peroxide and strontium peroxide. This study is part of this second approach and the fuels chosen were iron and zinc powders, mainly for chemical reasons (including the potential for use of thermomagnetometry on the iron systems), but also for possible environmental advantages. The mixed oxide products of pyrotechnic combustion could also have some scientific and/or commercial value. The techniques used included thermal analyses of mixtures and their individual components, and measurements of temperature-time profiles during combustion. Thermodynamic and kinetic information was obtained under a variety of conditions and scanning electron microscopy and X-ray diffraction and microprobe analyses provided additional information. Possible mechanisms of reactions are discussed in detail. The practical conclusions were that any potential use which the Fe/peroxide systems may have as delay compositions, with burning-rates of from 3-30 mm sâ »Â¹, is offset by the susceptibility of the oxidants to reaction with water and COâ‚‚ in the atmosphere. The Zn/BaOâ‚‚ and Zn/SrOâ‚‚ systems did not burn under compaction, and combustion of uncompacted powders was erratic. Zinc liquid (and probably zinc vapour) take part in the reaction and the gaseous nature of the combustion makes zinc-fuelled pyrotechnic systems unsuitable for delay applications. All the techniques used showed the heterogeneity of the solid residues of combustion. If these residues were to be of any value, they would need further conventional treatment involving grinding of the residue, possible adjustment of compositions, and calcining to produce uniform materials.
Keywords: Detonators; Peroxides; Chemistry, Analytic